Influence of Substance Abuse on Moral Development Among Secondary School Students in FCT, Abuja, Nigeria: The Moderating Role of NDLEA Intervention Programmes - Fatima Abiola Popoola (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the influence of substance abuse on moral development among secondary school students in the Federal Capital Territory (FCT), Abuja, Nigeria, with particular reference to the moderating role of intervention programmes of the National Drug Law Enforcement Agency. Substance abuse among adolescents has become a growing concern due to its negative implications on behavioral adjustment, academic performance, and moral development. The study was guided by Problem Behaviour Theory and Kohlberg’s Theory of Moral Development, which explain substance abuse as part of a broader pattern of maladaptive behaviours and highlight the stages of moral reasoning among adolescents. The study adopted a descriptive survey research design. The population comprised secondary school students in FCT, Abuja, while a sample was selected using an appropriate sampling technique. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics. The findings revealed that substance abuse has a significant negative influence on moral development among secondary school students. It was also found that students exposed to NDLEA intervention programmes demonstrated better awareness of the dangers of drug abuse and exhibited relatively improved moral behaviour compared to those not exposed. The study further established that NDLEA intervention programmes play a moderating role by reducing the strength of the relationship between substance abuse and poor moral development through drug education, school outreach, counselling services, and community sensitization. However, the persistence of substance abuse among students suggests that these interventions require strengthening in terms of coverage, consistency, and engagement strategies. The study concluded that substance abuse significantly undermines moral development among secondary school students in FCT, Abuja, while NDLEA intervention programmes have the potential to mitigate its effects when effectively implemented. It was recommended that NDLEA should intensify school-based drug education programmes, strengthen collaboration with schools and parents, and expand counselling and preventive interventions to enhance students’ moral and behavioral outcomes.